P507 United States and European patient perspectives on the impact of moderate-to-severe Ulcerative Colitis on sexual activity: Communicating Needs and Features of IBD Experiences (CONFIDE) survey. (30th January 2023) - Travis, S; Bleakman, A; Dubinsky, M; Rubin, D; Panaccione, R; Hibi, T; Kayhan, C; Gibble, T H; Sapin, C; Flynn, E; Atkinson, C; Schreiber, S
Abstract: Background: Patients with ulcerative colitis (UC) report that UC negatively affects their quality of life (QoL), including sexual functioning, satisfaction, and drive. 1, 2 These effects are rarely discussed with or by gastroenterologists in clinical practice. The CONFIDE study aims to elucidate the impact of symptoms on the lives of patients with moderate-to-severe UC in the United States (US), Europe (EU5; France, Germany, Italy, Spain, and UK), and Japan. Data presented here are from the US and EU5. Methods: Online, quantitative, cross-sectional surveys were conducted (July–September 2021). Criteria based on previous treatment, steroid use, and/or hospitalization were used to define moderate-to-severe UC. Data collected included patient perspectives on the impact of UC on sexual activity. Sexual activity was not limited to intercourse and included activities such as masturbation. Results: Surveys were completed by 200 US patients (male [M]=62%, mean age 40 years) and 556 EU5 patients (M=57%, mean age 39 years). Of these, 77% US and 54% EU5 patients were receiving advanced therapy (biologic/novel oral) and 52% and 73% were receiving steroids at the time of survey completion, respectively. Overall, 63% US patients (M=55%, female [F]=77%) and 53% EU5 patients (M=47%, F=60%) reported avoiding or decreasing sexual activity due to UC in the 3 months prior to the survey (Figure 1a). Among these patients (US: N=126; EU5: N=292), most frequently reported reasons for avoidance of sexual activity were bowel urgency (BU; 41%), decreased sexual desire (37%), and fear of BU-related accidents (34%) in the US and fear of faecal seepage (37%), fear of BU-related accidents (36%), and BU itself (31%) in EU5 (Figure 1b). Although reasons for avoiding sexual activity were broadly similar between sexes, higher percentage of male patients from both US and EU5 (US: M=33%, F=24%; EU5: M=42%, F=33%) reported fear of faecal seepage as a factor affecting sexual activity. Conversely, higher percentages of female patients reported perianal pain (M=13%, F=19%) and self-consciousness (M=13%, F=24%) as reasons for avoiding sexual activity in the US and decreased sexual desire (M=16%, F=26%), BU (M=26%, F=36%) and fatigue (M=14%, F=22%) in EU5 (Figure 2). Conclusion: In both US and EU5 populations, >50% patients with moderate-to-severe UC reported avoiding or decreasing sexual activity due to UC, with bowel urgency and bowel urgency-related accidents being among the top three reasons. In addition to other QoL parameters, impact of UC on patients' sexual health needs to be assessed in routine clinical practice. References: 1 Bulut AE, et al. Turk J Gastroenterol . 2019;30:33-39. 2 Jedel S, et al. Inflamm Bowel Dis. 2015;21:923-38.